The family Caprellidae (Amphipoda: Caprelloidea: Caprellidae) from Campos Basin, Southwestern Atlantic, with a key of species occurring in Brazil - Mauro, Fábio Da Motta; Serejo, Cristiana Silveira (Zootaxa, 2015)
Caprellid material of the present study was collected between 25–3000 m depth from the Campos Basin area, Southwestern Atlantic. As a result, Deutella incerta was found as a new record to the Southwestern Atlantic and two new species are described: Liropus guerragarciai sp. nov. and Mayerella sittropiae sp. nov. Besides, Paracaprella pusilla is herein redescribed as a common component of the Campos Basin amphipod community. Caprellids are a diverse and abundant group that can be found among algae and general biological substrates of the continental shelf area. As more deep sea samples are coming into light, they are turning out to be also a common component in this habitat. Including the present data, there are 25 caprellid species recorded in Brazil, being four of them restricted to the slope areas and 14 endemic to the Brazilian coast. A key to the Caprellidae species from Brazil is provided.